Preparatory Document Structuring Technique - Puspitarani, Yan; Surtia Zulpratita, Ulil (International Journal of Psychosocial Rehabilitation, 2020)
The need for mining structured data has increased in the past few years. This structured data is used as input for data mining tasks. Text mining is part of data mining where the data used is in the form of unstructured text. Text mining can be able to handle unstructured or semi-structured data sets such as emails, HTML files, full text documents, etc. Unstructured data usually refers to information that does not reside in a traditional row-column database, and it is the opposite of structured data. In order to extract information from text, preprocessing steps are needed.This paper discussed the theoretical basis of preprocessing documents for text mining. Brief descriptions of some representative approaches, such as NLP tasks and information extraction, are provided as well.